2016
DOI: 10.4149/bll_2016_010
|View full text |Cite
|
Sign up to set email alerts
|

Combination effect of melatonin and dexamethasone on liver ischemia/reperfusion injury

Abstract: OBJECTIVE: Liver failure following ischemia-reperfusion (I/R) injury is a major concern in liver surgery. The purpose of this study was to evaluate combination pretreatment with melatonin (MEL) and dexamethasone (DEX) on liver I/R model. Male Wistar rats (n = 60) were assigned to 5 groups of 12 animals each: (1) Sham: laparotomy without I/R; (2) I/R: hepatic I/R; (3) I/R+MEL: hepatic I/R+melatonin injected intraperitoneally (20 mg/kg); (4) I/ R+DEX: hepatic I/R+ dexamethasone injected intravenously (10 mg/kg);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 49 publications
1
24
0
1
Order By: Relevance
“…Greenwald et al found that neutrophils destroyed the hyaluronic acid of synovial fluid by producing ROS (30). Taghizadieh et al also showed that dexamethasone reduced the production of MDA and maintained the level of the antioxidant enzyme in liver during I/R (31). Dexamethasone ameliorates MDA, so it indirectly exerts an antioxidative effect, which can be confirmed by our results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Greenwald et al found that neutrophils destroyed the hyaluronic acid of synovial fluid by producing ROS (30). Taghizadieh et al also showed that dexamethasone reduced the production of MDA and maintained the level of the antioxidant enzyme in liver during I/R (31). Dexamethasone ameliorates MDA, so it indirectly exerts an antioxidative effect, which can be confirmed by our results.…”
Section: Discussionsupporting
confidence: 88%
“…Glucocorticoids can limit the inflammatory damage to the glycocalyx by suppressing the production of cytokines and chemokines and also through preventing the infiltration of inflammatory cells into tissues and mast cell degranulation. In a sample of isolated heart, hydrocortisone was able to significantly inhibit destruction of the endothelial surface layer after ischemia and during reperfusion and reduce TNF-α induction (31). In this study, we demonstrated that dexamethasone reduced parenchymal cell injury (reduction of ALT and AST) and also significantly ameliorated the glycocalyx damage in the group DEX + IR.…”
Section: Discussionmentioning
confidence: 49%
“…The difference in the doses of glucocorticoids may affect the expression of GPX1, GPX4, MnSOD, SOD1, SOD2 and other antioxidants in pregnant animals at different time points 45 . In addition, high-dose glucocorticoids can also reduce the expression of SOD and GPX in cells such as macrophages and skeletal muscle 46 . Clinical trials have confirmed that patients with long-term hormone therapy, postmenopausal therapy, and primary osteoporosis have low levels of GPX and SOD 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Liver failure subsequent ischemia-reperfusion (I/R) injury is recognized as a main difficulty in liver surgery [ 91 ]. Melatonin is a powerful endogenous antioxidant that possesses a protective role in liver I/R injury [ 92 , 93 ].…”
Section: Protective Effects Of Melatonin On Liver Injuriesmentioning
confidence: 99%